Centro comunitario en memoria del conflicto armado colombiano (2021)
Stereotomy in architecture represents the continuity in materials, in hiding the interior and always being linked to the earth as in time, being the living image of a stony and dark cave, nevertheless, the current buildings are in constant search of the light, ventilation and communication with the environment for the comfort of the users. This thesis proposes a community center in memory of the Colombian armed conflict for the reconstruction of dialogue and peace, located in the municipality of San José del Guaviare, in which a building is developed that represents a refuge for the victims of the territory, as it is understood that a cave does; but achieving that the internal spaces are always in exploration of the natural illumination and the ventilation by means of routes of water and abundant vegetation therefore to put in practice the concept of stereotomy achieving the continuity of the land in the construction and thus to have the perception that this is born of the same land.